CO preferential oxidation on cordierite monoliths coated with Co/CeO2 catalysts - Gómez, Leticia Ester (2012)
Cordierite monoliths washcoated with Co/CeO2 catalysts prepared from different methods were studied for the CO preferential oxidation reaction. Powder catalysts were also studied for the sake of comparison and in order to select the best formulations to prepare the catalytic coatings. High ? Co loaded catalysts resulted in good CO conversions and they showed Co3O4 as the main cobalt containing phase. A powder catalyst with low Co loading (below the solubility limit of cobalt in CeO2) was also prepared, but the behavior in the reaction under study was poor indicating that the segregation of Co3O4 was beneficial. For high Co loaded powders (10 wt.%), two different ways were used for the catalysts under preparation, namely wetness impregnation (WI) and co-precipitation (CP). The Co10(CP) catalyst showed somewhat higher CO conversions than the Co10(WI), probably due to the better redox capacity of the former, as seen in the TPR experiments. Taking into account these results, three cordierite ? washcoated catalysts were prepared with high Co loading. C1 and C2 were obtained by CeO2 washcoating followed by cobalt impregnation. In the first case, Ce oxide particles were obtained from a nitrate solution and in the second, a Nyacol suspension was used. A third sample was prepared (C3) using a slurry of a co-precipitated Co10(CP) catalyst. Monolith C3 showed the best CO conversion, although the difference with the other catalysts was not so evident as the one observed for the powder formulations. The mechanical stability, measured by ultrasound tests, was good for all monolithic catalysts and monolith C1 showed no-deactivation after 100 hours of time-on-stream at 190°C. The structured catalysts prepared were characterized by XRD, TPR, LRS, SEM and XPS, showing that their physical-chemistry features depend on the preparation method and Co loading.